Strategi pengelolaan kamar operasi pada instalasi bedah rumah sakit Eria Bunda Pekanbaru yang berwawasan lingkungan - Tyas Handayani; Yusni Ikhwan Siregar; Dedi Afandi (EcoNews, 2022)
The hospital is a place with a high degree of contamination, many pathogen germs that are in the environment are carried into the hospital and spread through activities in the hospital. About 10-20% of Nosocomial infections are caused by poor air quality. Initial observations obtained from RSIA Eria Bunda show that the Hospital Operating Room is still not in accordance with environmental health standards. Other observations obtained are inadequate lighting and humidity. Various physical environmental conditions that have not been optimal will be at risk of becoming a place of growth and development of bacteria. The growth of bacteria in the air that exceeds the standard will cause air quality to be not good, so it will cause health problems for both patients and hospital medical personnel. Based on this phenomenon, an environmental management strategy is needed in the Operation room to monitor air quality in the Operating Room. This research was carried out with a mixed research approach with survey methods, data collection was carried out by direct observation, measuring the temperature and humidity of the operating room and filling out questionnaires to find out the comfort of officers while working. After that, the determination of operating room management strategies on environmentally sound surgical installations using SWOT Analysis is carried out. The result of the study is that the measurement of Humidity and Lighting parameters is still below the operating room quality standards while the temperature parameters and air germ numbers are above the threshold of quality standards based on Permenkes No. 7 of 2019. For the results of the SWOT analysis RSIA Eria Bunda is in a strong internal position and responds to the opportunities that exist to avoid threats. The strategy used by S-O is to increase management capacity in carrying out supervision, improving the quality and maintenance of space, and improving education and information to employees.